Negotiating whiteness: a discourse analysis of students' descriptions of their raced experiences at Rhodes University, Grahamstown,1 South Africa - Msomi, Zuziwe Nokwanda (African Studies, 2021)
Questions of the dominance of cultures of whiteness are pre-imminent issues in historically white South African universities. Even when historically white universities – such as Rhodes University, the site of study for this thesis – have a predominantly black student body post 1994, there are still reports of students experiencing such institutions as alienating and excluding due to the privileging of whiteness. This thesis draws on the significant role played by discourse in how the world is constructed and reconstructed, to better understand how whiteness may continue to be produced and reproduced in everyday interactions at a historically white South African university, and how some students may feel less at home than others within such institutions. The thesis seeks to answer the following research question: what discursive strategies do Rhodes University students use to describe their raced experiences, and what role do these strategies play in either reinforcing and or challenging a culture of whiteness? The thesis engages with and is informed by literature on whiteness as constitutive of both social aspects and phenotypical essence. Drawing primarily from discourse analysis tools, and from interviews with Rhodes University students completed between 2014 and 2015, the thesis argues that whiteness is far from being a zero-sum game of winners and losers. Rather, there are gradations of whiteness where speakers draw upon whatever capital (social, phenotypical or a combination of both) to attain the best possible outcome for themselves. The thesis therefore takes seriously the idea that whiteness is a social construct which can, through socialisation be acquired, lost and, in some cases, decanted partially into other vessels. Whiteness, the thesis argues, is ever incomplete and subject to change as the context changes in order to ensure that it remains associated with privilege, opportunity and power. If whiteness is not limited to white bodies only, as suggested by both the data and literature review, then it must be studied in relation to blackness as well. The interactional, inter-relational and inter-racial construction and use of whiteness both methodologically and conceptually is one of the key contributions to the field of whiteness studies made by this thesis. This open-ended, permanent work in progress approach to whiteness can be the beginning of conversations about race that are not necessarily bounded by phenotype or essence – especially in South Africa, where race and a fixation of rigid social categories continue to be a central part of how South Africans navigate and understand the world around them.